Model Komunikasi Kesehatan Mental Berbasis Logoterapi dalam Membangun Konsep Diri Anak Panti Asuhan - Haloho, Heppy New Year; Parlindungan, Davis Roganda; Astono, Anjar Dwi; Andika, Rama; Purba, Reonald Purnama (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This study aims to describe the mental health communication model with a Logotherapy approach in an effort to build a more positive self-concept of foster children in LKSA or orphanages and identify what are the inhibiting and supporting factors. Descriptive qualitative research approach with case study method. Data collection through interviews, observations and FGDs. For data analysis using the Miles, Huberman, and Saldana method through stages, namely, data collection, data condensation, data presentation, and conclusions or verification. The results showed that there are two communication models applied at LKSA Dorkas in building the mental health of foster children, namely one-way communication (Paternalistic Model) and two-way (Informed Model). One-way communication is applied through parenting and character development programs such as Public Speaking, Coding and Character Building. While the two-way communication model is applied in daily assistance by caregivers, counseling with psychologists and mentoring sessions by coaches from YKAA. Supporting factors include interpersonal communication between caregivers and foster children, collaboration with external partners and character education programs. Meanwhile, the inhibiting factors are the limited human resources of caregivers, negative self-ideal in foster children and the social stigma of orphanage children.